Estimating consumption and changes in stock applying micro expenditure data - Bente Halvorsen (Statistics Norway, Research Department, 2009)
The consumption of storable goods does not necessarily equal purchases during a period because of changes in stock. In many cases, we have information about expenditures only, not consumption. A method is developed to obtain an estimate of consumption and changes in stock when only expenditure data are available. In addition to expenditure data, the method requires discrete information about the utilization of available equipment complementary to the storable good in consumption. Household energy consumption is used as an illustration, applying data from the Norwegian survey of consumer expenditure.
Keywords: C34; D12; Q41; 330; Storable goods; consumption; changes in stock; stochastic Kuhn-Tucker; Double Hurdle model; multivariate distribution